Effects of supplementation of different selenium sources on lipid profile, selenium, and vitamin E concentration of yolk - Hemly, N.I.M.; Zainudin, N.N.; Muhammad, A.I.; Loh, T.C.; Samsudin, A.A. (Springer Science and Business Media, 2024)
Egg preference as a source of protein also provides beneficial fatty acids, vital for human consumption. However, rich in lipid products are prone to oxidative damage. The study aims to determine the effect of supplementing biogenic selenium (Se) from Stenotrophomonas maltophilia, ADS18 (ADS18) in laying hens’ diet on yolk lipid oxidation status (MDA), beta-carotene (β-carotene) content, cholesterol, fatty acids, Se, and vitamin E (VE) level. A total of one hundred and twenty (120) laying hens of Lohmann Brown strains aged 50 weeks, weighing 1500 to 2000 g were reared individually in A-shape two-tier stainless-steel cages sized 30 cm x 50 cm x 40 cm (width, depth height). The hens were randomly allotted into four treatments with six replications in a complete randomised design for the period of 12 weeks. The basal diet contains 100 mg/kg VE. Treatment diets consist of basal diet as control, SS containing 0.3 mg/kg sodium selenite, Se-yeast containing 0.3 mg/kg selenised yeast, and VADS18 containing 0.3 mg/kg of ADS18. Forty-eight eggs were collected and freeze-dried biweekly for analysis. The results of the present study showed that hens supplemented ADS18 had significantly (P < 0.05) lower MDA and cholesterol levels while their egg yolks had higher levels of Se and mono-unsaturated fatty acids (MUFA). The control group had significantly (P < 0.05) higher saturated fatty acid (SFA) contents than the VE and dietary Se-supplemented groups, while the ADS18 group had the lowest SFA contents. Conversely, in comparison to the inorganic and control groups, the VE content of the egg yolk was significantly (P < 0.05) higher in organic Se-supplemented (Se-yeast and VADS18) groups. Hens with SS supplementation had significantly (P < 0.05) higher egg yolk β-carotene content. When compared to other treatment groups, the control group had higher (P < 0.05) polyunsaturated fatty acids (PUFA) content. The ADS18 is therefore deemed comparable to other Se sources. To prevent Se toxicity, however, a better understanding of the levels of ADS18 incorporation in poultry diets is required.